Step-by-Step Cadaver Dissection and Surgical Technique for Compartmental Tongue and Floor of Mouth Resection - Grammatica, Alberto; Piazza, Cesare; Ferrari, Marco; Verzeletti, Vincenzo; Paderno, Alberto; Mattavelli, Davide; Schreiber, Alberto; Lombardi, Davide; Fazio, Enrico; Gazzini, Luca; Giorgetti, Giovanni; Buffoli, Barbara; et al. (Frontiers in Oncology, 2021)
Background The aim of oral cancer surgery is tumor removal within clear margins of healthy tissue: the latter definition in the literature, however, may vary between 1 and 2 cm, and should be intended in the three dimensions, which further complicates its precise measurement. Moreover, the biological behavior of tongue and floor of mouth cancer can be unpredictable and often eludes the previously mentioned safe surgical margins concept due to the complexity of tongue anatomy, the intricated arrangements of its intrinsic and extrinsic muscle fibers, and the presence of rich neurovascular and lymphatic networks within it. These structures may act as specific pathways of loco-regional tumor spread, allowing the neoplasm to escape beyond its visible macroscopic boundaries. Based on this concept, in the past two decades, compartmental surgery (CS) for treatment of oral tongue and floor of mouth cancer was proposed as an alternative to more traditional transoral resections. Methods The authors performed three anatomical dissections on fresh-frozen cadaver heads that were injected with red and blue-stained silicon. All procedures were documented by photographs taken with a professional reflex digital camera. Results One of these step-by-step cadaver dissections is herein reported, detailing the pivotal points of CS with the aim to share this procedure at benefit of the youngest surgeons. Conclusions We herein present the CS step-by-step technique to highlight its potential in improving loco-regional control by checking all possible routes of tumor spread. Correct identification of the anatomical space between tumor and nodes (T-N tract), spatial relationships of extrinsic tongue muscles, as well as neurovascular bundles of the floor of mouth, are depicted to improve knowledge of this complex anatomical area.